Brand Equity PT Pos Indonesia (Persero) - Purba, Desima Fitriani; Franky Okto Bernando (SEAN Institute, 2024)
The purpose of this study is to examine the brand equity of Pos Indonesia. The researchers employed descriptive analysis techniques, including interval class ranges and data processing through means, range, and mean differences. This study employed a sample of 200 customers of Pos Indonesia in Jakarta. The data was collected by distributing questionnaires using Google Forms. The purpose of this research was to examine brand equity, specifically focusing on four dimensions: brand awareness, brand perceived quality, brand association, and loyalty. Brand refers to the unique identity and reputation of a product or company. Brand loyalty is the tendency of customers to choose and support a certain brand above others consistently. The descriptive analysis of the brand equity condition of the Pos Indonesia Main Branch Office yielded an overall mean score of 3.66. This score indicates that all consumers agreed in perceiving the company's brand equity. Starting from the highest, the brand association dimension reveals the outcomes of each level. The top dimensions of brand equity in the brand association dimension are brand association (3.86), perceived quality (3.81), and brand awareness (3.75). Customers perceive these three aspects as aligning with the three dimensions of brand equity. Additionally, brand loyalty, which scored 3.23, was perceived by customers as strongly indicating their loyalty towards Pos Indonesia. This research is constrained by the fact that it only includes postal users residing in the DKI Jakarta region. This research is expected to serve as a benchmark for future studies and offer valuable insights for organizations to shape their policies and explore alternative solutions.